3D paleotectonic stress field simulations and fracture prediction for marine-continental transitional facies forming a tight-sandstone reservoir in a highly deformed area. (18th April 2018) - Yin, Shuai; Jia, Qiang; Ding, Wenlong
Abstract: Marine-continental transitional facies coal measures that form tight sandstone reservoirs in heavily deformed areas are a new field for natural gas exploration. The degree of fracture development is the core factor in the enrichment of the potential natural gas resources. In this paper, using the Shanxi Formation in southern Qinshui Basin of eastern China as an example, the characteristics of fracture development in tight sandstone reservoirs were studied, and the paleotectonic stress field was reconstructed. On this basis, the fracture development of the area was predicted. The results show that fractures of different scales were developed in the tight sandstone of the Shanxi Formation and that over 90% of these fractures are tectonic. The types of fracture filling in the tight sandstone of the Shanxi Formation are mainly unfilled and half-filled. Fine geological modeling and paleostress simulations were conducted on the II sand group of the Shanxi Formation using the 3D finite element method. The geostress field of the target layer in the Himalayan period was restored. Considering that the tensile and shear fractures of the target layer were both well developed, we constructed a comprehensive rupture rate ( I F ) to quantitatively predict the level of development of the fractures by combining the Griffith tensile failure criterion and Mohr–Coulomb shear failure criterion. The prediction results are in agreement with the actual geological conditions, which indicates that this method is suitable for characterizing the fractures in marine-continental transitional facies coal measures that form tight sandstone reservoirs in heavily deformed areas.